LAMPUNG PROVINCIAL GOVERNMENT SYNERGY AND BNN IN P4GN PROGRAM - Sri Riski; Damanhuri WN (Law Faculty of Universitas Bandar Lampung, 2021)
The regulation regarding narcotics is currently regulated especially in the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics. In the Narcotics Law, narcotics are divided into 3 groups which are further mentioned in the attachment to the law (Article 6 of the Narcotics Law). To eradicate the abuse of narcotics in Indonesia, a Badan Narkotika Nasional, or abbreviated as BNN, was established (Article 64 Paragraph (1) of the Narcotics Law). In carrying out their investigative duties, investigators of the National Narcotics Agency (BNN) have the authority, among other things; to search and conduct tests of urine, blood, hair, and other body parts (Article 75 letters e and 1 of the Narcotics Law).